Inhibitory effects of non-steroidal anti-inflammatory drugs on the binding of prostaglandins to human serum albumin - Huo Yi-nian; Wang Zhen-gang; Jin Yin-chang (Acta Pharmacologica Sinica, 2016)
This paper deals with the influence of some acidic nonsteroidal anti-inflammatory drugs(NSAID)(sodium salicylate, aspirin, indomethacin,ibuprofen and phenylbutazone) and other agents(chlorpromazine, eutonyl, cocaine, procaine, benzocaine, gossypol, etc.) on the binding of [3H]PGE1, [3H]PGF2alpha and [3H]PGA1 to human serum albumin(HAS) determined by equilibrium dialysis. With adequate concentrations(0.1-10 mM) all the acidic NSAID significantly inhibited the binding of the [3H]PG to HSA. The nonanti-inflammatory drugs which inhibited prostaglandin synthesis showed no significant inhibitory activity on prostaglandin binding to HSA.